A decision support system for methods of measurement in construction projects - Magdy, Abdelrahman (AUC Knowledge Fountain, 2016)
The standard Methods of Measurement is an important topic when it comes to the process of the preparation of the Bill of Quantities of a construction project. This is because the Method of Measurement provides a set of guidance rules to prepare the bill that could have less discrepancies decreasing the risk of having problems during the cost control of the construction project during execution. This paper is for developing a decision support system for choosing the suitable standard Method of Measurement for a construction project based on certain project parameters. Three popular international standard MOMs are researched which are the CESMM for civil projects, NRM for building projects and POMI for different project types and their usage in the Middle East is investigated. The literature review is explored to present main information about the characteristics and usage of the each method. Data about the method of measurements usage is then collected through a questionnaire distributed among a sample of quantity surveying professionals in the Middle East. An expert system in the form of a decision model is created that automates the process of the Method of Measurement selection for different projects in the Middle East based on five project parameters which are the project type, client and contractor’s nationality compared to the country where the project is executed, project value and contract type. This model is then verified to check its logic and validated through case studies of real life projects and comparing the model choice of the suitable Method of Measurement for a certain project with the one actually used in that project and then the results are explained. Finally, a conclusion is reached regarding the use of the three MOMs in the Middle East and that they are recognized with POMI and CESMM as the most recognized ones. Also, the model created may be suitable for choosing the suitable method of measurement for civil projects unlike building projects since NRM is still a new method which is still not used in projects. This conclusion is followed by a list of recommendations to improve the future research such as improving the model by adding more project parameters and also recommendations to serve the topic of standard Methods of Measurement within the professional field like making future researches to develop codes for some Middle Eastern companies as Egypt.